2015
DOI: 10.1155/2015/806368
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI in Patients with Unilateral Bloody and Serous-Bloody Nipple Discharge: A Comparison with Galactography

Abstract: Purpose. Assessing the role of breast MRI compared to galactography in patients with unilateral bloody or serous-bloody nipple discharge. Materials and Methods. Retrospective study including 53 unilateral discharge patients who performed galactography and MRI. We evaluated the capability of both techniques in identifying pathology and distinguishing between nonmalignant and malignant lesions. Lesions BIRADS 1/2 underwent follow-up, while the histological examination after surgery has been the gold standard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…Our results are consistent with the pooled sensitivity reported in a recent meta-analysis [29]. Our specificity (90%, [45/50]) and PPV (84.3%, [27/32]) were higher than the values reported previously with the exception of findings reported by Manganaro, et al [19]. In part the excellent diagnostic performance achieved in our study can be ascribed to the use of a 3.0 Tesla magnet rather than a 1.5 Tesla magnet for which sensitivity and specificity values in patients with ND have ranged from 60-95% and 44-79%, respectively [7,10,22,31].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with the pooled sensitivity reported in a recent meta-analysis [29]. Our specificity (90%, [45/50]) and PPV (84.3%, [27/32]) were higher than the values reported previously with the exception of findings reported by Manganaro, et al [19]. In part the excellent diagnostic performance achieved in our study can be ascribed to the use of a 3.0 Tesla magnet rather than a 1.5 Tesla magnet for which sensitivity and specificity values in patients with ND have ranged from 60-95% and 44-79%, respectively [7,10,22,31].…”
Section: Discussionsupporting
confidence: 93%
“…As noted by Mann, et al [30] whereas unenhanced MRI can differentiate lesions and abnormalities of the breast, administration of a gadolinium-containing contrast material is needed to accurately diagnose or exclude a cancer. In our study MRI showed high sensitivity (93.1%, 27/29) for breast lesion detection and diagnosis, supporting numerous previous studies that have confirmed dynamic contrast enhancement MRI as the most sensitive diagnostic approach for breast cancer detection [7,8,19]. Our results are consistent with the pooled sensitivity reported in a recent meta-analysis [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, MRI should be considered in cases in which other approaches have failed to identify an underlying cause of pathologic nipple discharge [3,23,24,[53][54][55]. The sensitivities of breast MRI for detection of underlying cause of pathologic nipple discharge are 86% to 100% for invasive cancer and 40% to 100% for noninvasive disease [3,24,46,53,55,56]. Bahl et al [56] reported the sensitivity, specificity, PPV, and NPV of MRI for detection of malignancy in patients with pathologic nipple discharge to be 100%, 68%, 37%, and 100%, respectively.…”
Section: Mbi and Fdg-pem If Patient History And Physical Examinationmentioning
confidence: 99%
“…☢☢ Image-guided core biopsy breast 1 See references [5,10,12,24,31,40,41,49,58,59,63]. [3,8,23,24,35,46,[51][52][53][54][55]. B…”
mentioning
confidence: 99%